Effects of sodium metabisulphite and citric acid on the shelf life of fresh cut sweet potatoes - Sgroppo, S. C.; Vergara, L. E.; Tenev, M. D. (Spanish Journal of Agricultural Research, 2010)
Minimally processed vegetables are products susceptible to chemical and biological changes, thus becoming highly perishable. During sweet potatoes (Ipomoea batatas Lam.) processing, some deteriorative reactions occur affecting quality, mainly change of color. The purpose of this research is to avoid or minimize this deterioration, so the effects of application of chemical agents to fresh cut and refrigerated stored sweet potatoes were studied, evaluating the occurrence of major organoleptic, physicochemical and nutritional changes and assesing the sensory acceptability. Tests were done with sweet potato variety 'Colorada Correntina', which were treated with sodium metabisulphite/citric acid (pH = 2.91), arranged in polystyrene trays film, coated with PVC, and stored at 5°C and 10°C. Variations on the titratable acidity, pH, total sugars and ascorbic acid were registered and the surface color was evaluated through digital image analysis. The final product acceptability was determined through sensory evaluation and microbiological counts carried out at the beginning and at the end of the assays. During storage, there were slight changes in physicochemical characteristics such as absorbic acid and sugar content and in surface color as well. The microbial counts were lower than the fixed levels established by the Spanish legislature. The sensory attributes were rated as «acceptable » by consumers. Finally it is possible to assert that sweet potato 'Colorada Correntina' minimally processed and treated with sodium metabisulphite 2%/citric acid can be preserved, packaged and stored at 5°C for 14 days.